Synergistic effects of pyrite and sludge biochar enhancing performance and reducing greenhouse gas emissions in constructed wetland-microbial fuel cells - Wang Maosen; Qin Yangyi; Wu Haiming; Zhao Jianguo; Zheng Lihe; Ding Keyu; Wang Baogui; Du Jingjing (Bioresource Technology, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Research trends and hotspots of microalgae protein as a functional ingredient in plant-based foods: A bibliometric analysis based on the web of science - Jiayi He; Haoxie Xu; Keyu Lu; Chunli Guo; Ming Du; Ruochen Jia (Algal Research, 2026)

Oxygen vacancies and Li+ pre-embedding for magnesium storage in Anatase TiO2 toward magnesium/lithium hybrid batteries - Haofei Du; Xueyang Hou; Fan Cheng; Yifan Liu; Zhao Fang; Keyu Xie; Ling Zhang (Chemical Engineering Journal, 2025)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

Selective efficient photocatalytic degradation of antibiotics and direct Z-type migration pathway for hierarchical core–shell TiO2/g-C3N4 composites - Hu Liu; Jianmei Pan; Keyu E; Yi Guan; Wenbo Gou; Peng Wang; Shahid Hussain; Ze Du; Chengfei Ma (Environmental Science and Pollution Research, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

Identified trans-splicing of YELLOW-FRUITED TOMATO 2 encoding the PHYTOENE SYNTHASE 1 protein alters fruit color by map-based cloning, functional complementation and RACE - Lulu Chen; Wenzhen Li; Yongpeng Li; Xuechao Feng; Keyu Du; Ge Wang; Lingxia Zhao (Plant Molecular Biology, 2019)